The Influence of Corporate Governance and Financial Performance on Technology Sector Companies Listed on The Indonesia Stock Exchange in 2021-2022 - Saputri, Afra Diana Salsabila Untung; Handayani, Susi (PT Aksara Indo Rajawali, 2024)
This research aims to examine the influence of corporate governance and financial performance on the firm value in the technology sector listed on the Indonesia Stock Exchange for the 2021-2022 period. The sampling technique used purposive sampling for 37 companies. Data analysis uses multiple linear regression analysis. The research results show that independent commissioners and institutional ownership have a positive effect on firm value. Audit committee, ROA, and ROE have no effect on firm value. This, overall, it can be concluded from the results of this research that corporate governance is able to influence firm value while financial performance is not. Further research is recommended to expand the scope of the sectors studied and extend the research time span so that the results obtained are more comprehensive and applicable.